Perbandingan Efektifitas Metode Demonstrasi dan Video Terhadap Peningkatan Motivasi Remaja dalam Praktik Metode Sadari - Sulastri Sulastri; Sri Mintarsih; Sulis Susilawati (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
According to Pathological Based Registration data in Indonesia, breast cancer ranks first with a relative frequency of 18.6%. In Central Java Province, the number of cancer cases has increased significantly over time. In 2010, there were 13,277 cases of cancer, and in 2015 this number increased to 18,954 cases. Of these, 6,899 cases were cervical cancer (35.13%), while 9,542 cases were breast cancer. One of the early detection methods of breast cancer that is easy to do independently is a breast self-examination or known as Sadari. The application of this Sadari method can help women to be more sensitive to changes in their breasts so that the risk of delays in cancer treatment can be minimized. This study aims to determine the effectiveness of the demonstration method compared to video media in increasing adolescents' motivation to practice the Sadari method. The type of research used is quasi-experimental with pre-test and post-test design. The sampling technique was carried out by purposive sampling, with research instruments in the form of questionnaires consisting of items that are favorable and unfavorable. Data analysis was carried out using univariate and bivariate methods to determine the difference in motivation between the experimental groups. The results showed that in the group of the Sadari motivation experiment with video treatment, the significance value obtained was p = 0.000. The same was also shown in the group with the demonstration treatment, with a significance value of p = 0.000. Furthermore, the results of the Mann-Whitney test showed a significant value of 0.002. Since p < 0.05 (p = 0.002), it can be concluded that there is a significant difference in Sadari motivation between the video group and the demonstration. The average motivation score of the demonstration group (36.00) was higher than that of the video group (25.00), so the demonstration method was stated to be more effective in increasing Sadari's motivation.